Solve for x 2(x-7)=3x

Math
2(x-7)=3x
Simplify 2(x-7).
Tap for more steps…
Apply the distributive property.
2x+2⋅-7=3x
Multiply 2 by -7.
2x-14=3x
2x-14=3x
Move all terms containing x to the left side of the equation.
Tap for more steps…
Subtract 3x from both sides of the equation.
2x-14-3x=0
Subtract 3x from 2x.
-x-14=0
-x-14=0
Add 14 to both sides of the equation.
-x=14
Multiply each term in -x=14 by -1
Tap for more steps…
Multiply each term in -x=14 by -1.
(-x)⋅-1=14⋅-1
Multiply (-x)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1x=14⋅-1
Multiply x by 1.
x=14⋅-1
x=14⋅-1
Multiply 14 by -1.
x=-14
x=-14
Solve for x 2(x-7)=3x

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top